Humoral immune response to functional regions of human cytomegalovirus glycoprotein B - Navarro, David; Lennette, Evelyne; Tugizov, Sharof; Pereira, Lenore (Journal of medical virology, 1997)
Sera from patients with primary human cytomegalovirus (HCMV) infections, both acute and convalescent phase, and from HCMV‐seropositive healthy subjects were analyzed to determine whether the sera would recognize antigenic domains on HCMV glycoprotein B (gB) that function in virion infectivity and spread of virus from cell to cell. The intact gB molecule, amino‐terminal derivatives of different lengths, and internal deletion derivatives were expressed in eukaryotic cells and reacted by immunofluorescence with the sera. All convalescent‐phase sera and most sera from healthy seropositive individuals reacted with full‐length gB and with an amino‐terminal derivative containing 687 amino acids (aa), gB‐(1–687); approximately half of the sera recognized an amino‐terminal derivative of 447 aa, gB‐(1–447), and one‐third reacted with the shortest deletion derivative of 258 aa, gB‐(1–258). Of the acute‐phase sera, 77% recognized intact gB and gB‐(1–687), 32% recognized gB‐(1–447), and 14% recognized gB‐(1–258). Deletion of aa 548 to 618 dramatically reduced the percentage of reactive sera, whereas deletion of aa 411 to 447 had a minor impact on reactivity of sera. To investigate the epitope specificity of human antibodies to gB, we carried out competition experiments between human sera with neutralizing activity and selected monoclonal antibodies (mAbs) to conformational epitopes on gB. We found that antibodies in human sera preclude syncytium formation in UB15‐11 glioblastoma cells constitutively expressing gB and compete with certain murine mAbs that block virus entry into cells and transmission of infection from cell to cell. Our results show that HCMV‐immune human sera contain antibodies to functional regions on gB, and the abundance of these antibodies in convalescent‐phase sera suggests that they may play a central role in limiting dissemination of virus in the host. J. Med. Virol. 52:451–459, 1997. © 1997 Wiley‐Liss, Inc.